Remoção de fósforo em efluente por meio de adsorção em bentonita modificada, TechPhos® - Assis Abilio, Monica Cristina de (Universidade Federal de São Carlos, 2020)
Most of the human activities that use water produce effluents which can contain large amounts of contaminants, such as organic matter, nitrogen compounds, phosphates and metals. In developing countries, the vast majority of wastewater is discharged directly into the environment, without any kind of treatment. In Brazil, usually wastewater treatment plants perform only the primary and secondary stages and do not apply technologies to remove nitrogenous and phosphate compounds from their effluents. High concentrations of these compounds in the water bodies can cause damage to the aquatic life, especially phosphorus, the main responsible for eutrophication processes. Phosphorus is essential for the development of living organisms and is also used in a large scale for soil fertilization and world food production. Phosphorus used to manufacture fertilizers are extracted from phosphate rocks, which are non-renewable sources of this nutrient. The aim of this research is to investigate the removal of phosphorus from the effluent of the wastewater treatment plant Monjolinho of São Carlos city (WWTP Monjolinho), for the purpose of improving the quality of the effluent, protecting aquatic life and to propitiate an alternative of reusing this phosphorus for soil fertilization and plants nutrition. Phosphorus removal strategies were evaluated by struvite precipitation, precipitation as calcium orthophosphates and finally adsorption on a modified mineral clay (modified bentonite). Important parameters in the struvite crystallization process were evaluated, such as pH, concentration of constituent ions, agitation gradient and induction time, however the process proved to be unfeasible, because none struvite crystallization was observed. In the precipitation study of calcium orthophosphates, different pH values were carried out and evaluated, using a calcium source, also unsuccessful in the precipitation processes. Jartest tests were also performed with a mineral clay modified for phosphorus adsorption, and in combination with the application of polymer and polyaluminium chloride (PAC). From the adsorption kinetics and adsorption isotherm studies, the process proved to be favorable, obtaining a maximum adsorption capacity of 3.08 mg P g-1 of adsorbent. In view of the results, the feasibility of using modified bentonite for the removal of phosphate compounds in effluent was observed, with phosphorus removal of up to 97% in combination with PAC, thus obtaining an optimized condition for the removal of phosphorus in the effluent of WWTP Monjolinho.
Phosphorus removal in effluent by means of adsorption in modified bentonite, TechPhos®
Keywords: Estruvita; Fósforo (remoção); Esgoto sanitário; Adsorção; Bentonita modificada; Ferro; Struvite; Phosphorus (removal); Sanitary wastewater; Adsorption; Modified bentonite; Iron; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS::QUIMICA SANITARIA; ENGENHARIAS::ENGENHARIA SANITARIA::TRATAMENTO DE AGUAS DE ABASTECIMENTO E RESIDUARIAS::TECNICAS AVANCADAS DE TRATAMENTO DE AGUAS